Effect of ball milling time on the properties of nickel oxide-samarium-doped cerium composite anodes for solid oxide fuel cells. (21st June 2019) - Raduwan, Nor Fatina; Ali, S.A. Muhammed; Anwar, Mustafa; Muchtar, Andanastuti; Somalu, Mahendra Rao
The powder characteristics of composites under different processing conditions, such as milling time, must be elucidated before fabricating electrodes with porous structures for fuel cell applications. Milling time is an important parameter in producing pure composite powders with fine crystallite size and affects the densification of the sintered pellet and the electrical performance of the cell. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analyses were conducted to characterise nickel-oxide-samarium-doped cerium (NiO-SDC) powders milled for different durations (2, 12, and 24 h). Field-emission scanning electron microscopy (FESEM) analysis was performed to clarify the porosity of the sintered pellets. Density was determined using Archimedes method and was found to decrease after the reduction of the anode pellets. The XRD analysis of the composite anodes showed good chemical compatibility between the NiO and SDC. The TEM analysis of the as-prepared powders indicated that the particle size of the powder was within the nanometre range. This finding was confirmed by the FESEM micrograph of the sintered pellets. The porosity of the sintered pellets (before and after reduction) ranged from 20% to 40% and was considered sufficient for anode materials in solid oxide fuel cells (SOFC).